2023
DOI: 10.1079/hai.2023.0019
|View full text |Cite
|
Sign up to set email alerts
|

Parental status influences human-to-pet caregiving behaviors, attachment, and attitudes in a Finnish sample

Abstract: A growing body of literature suggests people are choosing to forego parenthood, bringing companion animals into the home as a focus for people’s attachment and caretaking behavior instead. This emergent “pet parenting” can be defined as the parent-like investment in companion animals and has been linked to countries that are experiencing or have experienced the Second Demographic Transition (SDT) marked by subreplacement fertility, changing marriage norms, increased educational attainment, and a flexible life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Thus, it would be important for future studies to assess the possible role of pet and human parenting in promoting or deterring human-pet co-sleeping practices. For example, Volsche et al 34 found that co-sleeping with pets was more common for participants who self-identified as non-parents (i.e., those who did not have or plan to have children) than those who were current parents or who intended to become parents in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be important for future studies to assess the possible role of pet and human parenting in promoting or deterring human-pet co-sleeping practices. For example, Volsche et al 34 found that co-sleeping with pets was more common for participants who self-identified as non-parents (i.e., those who did not have or plan to have children) than those who were current parents or who intended to become parents in the future.…”
Section: Discussionmentioning
confidence: 99%